2020
DOI: 10.1051/0004-6361/202037568
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of evolved stars to constrain the internal transport of angular momentum

Abstract: Context. The internal characteristics of stars, such as their core rotation rates, are obtained via asteroseismic observations. A comparison of core rotation rates found in this way with core rotation rates as predicted by stellar evolution models demonstrate a large discrepancy. This means that there must be a process of angular momentum transport missing in the current theory of stellar evolution. A new formalism was recently proposed to fill in for this missing process, which has the Tayler instability as i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Eggenberger et al (2019b) showed that values of α significantly below unity (α ∼ 0.5) are needed to reproduce the internal rotation of the evolved subgiants studied by Deheuvels et al (2014), while matching the core rotation of stars on the RGB requires α ∼ 1.5. Moreover, even higher values of α are needed to account for the internal rotation of intermediate mass stars in the core He burning phase (den Hartogh et al 2020). To estimate the agreement of this formalism with the results of this study, we computed a model of KIC5955122 including the prescription of Fuller et al (2019) using the GENEC code.…”
Section: Comparison With Predictions From Potential Am Transport Mechmentioning
confidence: 98%
See 1 more Smart Citation
“…Eggenberger et al (2019b) showed that values of α significantly below unity (α ∼ 0.5) are needed to reproduce the internal rotation of the evolved subgiants studied by Deheuvels et al (2014), while matching the core rotation of stars on the RGB requires α ∼ 1.5. Moreover, even higher values of α are needed to account for the internal rotation of intermediate mass stars in the core He burning phase (den Hartogh et al 2020). To estimate the agreement of this formalism with the results of this study, we computed a model of KIC5955122 including the prescription of Fuller et al (2019) using the GENEC code.…”
Section: Comparison With Predictions From Potential Am Transport Mechmentioning
confidence: 98%
“…So far, their impact on the rotation evolution of subgiants and red giants has been addressed only under the debated assumption of the Tayler-Spruit dynamo in radiative interi-ors (Spruit 2002), and its revision based on a different saturation process by Fuller et al (2019). Comparisons with asteroseismic measurements have shown that this process is currently unable to correctly account for the internal rotation of subgiants and red giants (Cantiello et al 2014, den Hartogh et al 2019, Eggenberger et al 2019b, den Hartogh et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature that tackles this important question, most of the attention has been given to the potential effects of Maxwell stresses triggered by unstable fields in stably stratified radiative regions (e.g. Fuller et al 2019;Eggenberger et al 2020;Den Hartogh et al 2020;Jouve et al 2020). Here we recall the potentially significant efficiency with which a stable axisymmetric field redistributes angular momentum along poloidal field lines, a well-known result since Ferraro (1937), Mestel & Weiss (1987).…”
Section: Angular Momentum Transport By Fossil Magnetic Fields In Evolved Solar-like Starsmentioning
confidence: 99%
“…The physical mechanism is not yet understood, but some characterization of its behavior with evolutionary status or mass have been performed (Cantiello et al, 2014;Spada et al, 2016;Eggenberger et al, 2017Eggenberger et al, , 2019a. The proposed solution of a modified Tayler-Spruit magnetic dynamo (Fuller et al, 2019) has been shown to be unable to reproduce the observations of both red giants and sub-giants (Eggenberger et al, 2019b;den Hartogh et al, 2020). Explorations of the role of IGW (see section 5.1) in the angular momentum transport in red giants and sub-giants have shown that they are not efficient enough to solve the problem, though they could play a role (Fuller et al, 2014;Pinçon et al, 2017).…”
Section: Rotationmentioning
confidence: 99%